The intimate relationships of mRNA decay and translation - Roy, Bijoyita (2013)
The decay rate of an mRNA and the efficiency with which it is translated are key determinants of eukaryotic gene expression. Although it was once thought that mRNA stability and translational efficiency were directly linked, the interrelationships between the two processes are considerably more complex. The decay of individual mRNAs can be triggered or antagonized by translational impairment, and alterations in the half-life of certain mRNAs can even alter translational fidelity. In this review, we consider whether mRNA translation and turnover are distinct or overlapping phases of an mRNA life cycle, and then address some of the many ways in which the two processes influence each other in eukaryotic cells.